Green Accounting, Intellectual Capital, Gender Diversity dan Kinerja Keberlanjutan Perusahaan - Wilang Ica Swari, Sang Ayu Putu; Ratna Sari, Maria Mediatrix (E-Jurnal Akuntansi; Vol 33 No 12 (2023), 2023)
This research aims to determine the influence of green accounting, intellectual capital, and gender diversity on Corporate Sustainability Performance (CSP). The population in the study consisted of companies listed in the SRI-KEHATI Index for the 2016-2020 period. The sample was determined using a purposive sampling technique, with a total sample of 12 companies. Multiple linear regression analysis is used to test the influence of green accounting, intellectual capital, and gender diversity on CSP. The results of this research show that green accounting, intellectual capital, and gender diversity have a positive effect on CSP. This research can support stakeholder theory and can provide additional information for consideration by stakeholders regarding decision making. Kata Kunci: Corporate Sustainability Performance, Green Accounting, Intellectual Capital, Gender Diversity